Students' Laziness in Doing School Assignments/Homework - Apriani (Tinta Emas Institute, 2023)
Education plays a crucial role in students' development, and the success of the learning process is highly dependent on teachers' understanding of students' learning problems. This research aims to identify and address students' learning problems in the area of learning. Through case studies, it was found that students like Vega experience learning disengagement, lack of motivation, and difficulty managing time. The analysis concluded that internal and external factors influenced the learning problems, including lack of parental attention and an unsupportive peer environment. Prognosis indicated that without treatment, students were at risk of getting low grades, declining learning achievement and falling behind. However, with appropriate treatment, students can overcome these problems, complete assignments on time, improve achievement and make their parents proud. Handling involves a personal approach, providing motivation, and collaborating with parents. Evaluation is done through making students aware of the problem, understanding the importance of completing assignments well, and active attention in learning. The obstacle in this research is the limited time due to the parallel tasks of Pendidikan Profesi Guru (PPG) Dalam Jabatan (daljab). Thus, this research provides a comprehensive picture of the identification, analysis and handling of student learning problems to improve the quality of learning.